Limiting rights and freedoms in the COVID -19 pandemic in Poland. Theory and practice (Discourse of Law and Administration, 2023)
The COVID-19 pandemic put the government in responsibility of protecting public health. Decisions restricting individual rights and freedoms were needed, this remains uncontested. However, the manner of their introduction raises controversy primarily from a constitutional and methodological point of view. The article analyses the legality of the restrictions on the rights and freedoms and the indicates the correct process of their implementation. The article also refers to the jurisprudence in the field of introduced restrictions.
Keywords: rights; fredo; COVID-19; Constitution; pandemic